Structural, Magnetic, Spectroscopic and Density Functional Theory (DFT) Analysis of Bis((1‐((E)‐2‐pyridinylmethylidene)semicarbazone)copper(II)sulfate) Dihydrate Complex. Issue 27 (22nd September 2017) - Soek, Rafel N.; da C. Gouveia, Tiago L.; Garbelini, Ellery R.; dos R. Crespan, Estela; Pineider, Francesco; Poneti, Giordano; Machado, Guilherme S.; Ribeiro, Ronny R.; Hörner, Manfredo; Nunes, Fábio S.
Abstract: Herein we describe the synthesis, structural, spectroscopic and magnetic characterization of a new pentacoordinated bicopper(II) complex containing 2‐formylpyridine semicarbazone (HSCpy), referred as complex1 . Each copper core is bound to one N, N, O‐ tridentate HSCpy ligand and connected to the second metal ion by two μ‐oxygen sulfato‐bridges. The compound shows an extensive association between the neutral complex molecule and water as crystallization solvate through classical N−H⋅⋅⋅O, O−H⋅⋅⋅O and, non‐classical C−H⋅⋅⋅O intermolecular hydrogen bonding generating a supramolecular 3‐D assembly in the solid state. Jahn‐Teller stabilization energies at 5144 cm −1 and spin orbit coupling constants λ=−442 cm −1 were estimated using the electronic spectra and Electron Paramagnetic Resonance data. The variable‐temperature (2‐300 K) magnetic measurements showed isotropic magnetic interaction between the two copper ions, according to the spin Hamiltonian yielding 2 J values at −0.34 cm −1 for complex1, in accordance with a very small antiferromagnetic interaction between copper ions kept apart by 3.24 Å. The results are compared to the thiosemicarbazone analogue. Abstract : Synthesis, structural, magnetic and spectroscopic (EPR‐UV‐Vis) characterization of a new pentacoordinated bicopper(II) complex containing 2‐formylpyridine semicarbazone (HSCpy) is discussed and compared with its tiosemicarbazone analogue.